Maritime Terrorism - Greenberg, Michael D.; Chalk, Peter; Willis, Henry H.; Khilko, Ivan; Ortiz, David S. (RAND Corporation, 2023)
Policymakers have become increasingly concerned in recent years about the possibility of future maritime terrorist attacks. Though the historical occurrence of such attacks has been limited, recognition that maritime vessels and facilities may be particularly vulnerable to terrorism has galvanized concerns. In addition, some plausible maritime attacks could have very significant consequences, in the form of mass casualties, severe property damage, and attendant disruption of commerce. Understanding the nature of maritime terrorism risk requires an investigation of threats, vulnerabilities, and consequences associated with potential attacks, as grounded both by relevant historical data and by intelligence on the capabilities and intentions of known terrorist groups. These risks also provide the context for understanding government institutions that will respond to future attacks, and particularly so with regard to the U.S. civil justice system. In principle, civil liability operates to redistribute the harms associated with legally redressable claims, so that related costs are borne by the parties responsible for having caused them. In connection with maritime terrorism, civil liability creates the prospect that independent commercial defendants will be held responsible for damages caused by terrorist attacks. This book explores risks and U.S. civil liability rules as they may apply in the context of these types of attacks.